Test report no. PLBO/6: wear tests of PERPRO tools grade CLV, machining meehanite - College of Aeronautics, (Cranfield) (College of Aeronautics, 1963)
Tools of grade CLV were tested at 300 fpm cutting speed, 0.010 in./rev. feed and 0.10 in. depth of cut to 0.030 in. flankwear. The results gave a mean tool life of 37 minutes which should be compared with the results given in Report No. PLB0/1 for grades CLV 403, A, B and C.